Hydraulic Performance of a Francis Turbine with a Variable Draft Tube Guide Vane System to Mitigate Pressure Pulsations - Jesline Joy; Mehrdad Raisee; Michel J. Cervantes (Energies, 2022)
The present paper demonstrates a proof-of-concept by introducing a variable guide vane system in the draft tube of a high-head Francis model turbine. The aim is to examine the hydraulic performance of the turbine while mitigating the pressure pulsations in the draft tube. The guide vanes can rotate about an axis up to ±45°. The pressure pulsations mitigation studies were performed at lower- and upper-part loads. The hydraulic performance was examined at all operating ranges within the turbine head. There were six guide vane configurations considered between ±45°. The findings demonstrate that the highest efficiency loss with a guide vane configuration that mitigates the pressure pulsations is marginal, with modest improvements at the best efficiency point. The pressure pulsations are 100% mitigated at the lower part load, and there is a maximum decrement in the pressure pulsations up to 80% at the upper part load. The study demonstrates that such a system can improve the operational flexibility of the hydro-turbine by mitigating the pressure pulsations and marginally affecting its hydraulic performance.